Toward a molecular design of porous carbon materials - Borchardt, Lars; Zhu, Qi-Long; Casco, Mirian E.; Berger, Reinhard; Zhuang, Xiaodong; Kaskel, Stefan; Feng, Xinliang; Xu, Qiang (Materials Today, 2017)
The molecular design of porous solids from predefined building blocks, in particular metal-organic and covalent frameworks, has been a tremendous success in the past two decades approaching record porosities and more importantly was an enabler for integrating predefined molecular functionality (enantioselectivity, optical and catalytic properties) into pore walls. Recent efforts indicate that this concept could also be applicable to rationally design porous and nanostructured carbonaceous materials, a class of materials hitherto and especially in the past often considered as “black magic” in terms of pore-wall structure definition and surface functionality. Carbon precursors with structural and compositional information in their molecular backbone, pre-formed covalent bonds, or integrated functional groups enable the design of carbon materials that can be tailored for certain applications. We review this exciting field of synthetic approaches based on molecular building blocks such as ionic liquids, bio molecules, or organic precursor monomers enabling the design of advanced carbonaceous architectures such as porous carbons, porous carbon-rich polymers or graphene nanoribbons. Moreover, our review includes approaches using the reactive and thermal transformation of periodic crystalline structures such as metal-organic frameworks, or carbides into equally defined carbon material. Such molecularly designed carbons are not only ideal model materials for fundamental science but also emerge in applications with until now unattained functionality.
CRIS-Team Scopus Importer:2022-04-14